VECTOR INTERPRETATION OF THE RADIO THERMAL FIELDS IN THE PROBLEM OF CORRELATION - EXTREMAL NAVIGATION OF AIRCRAFT ON GROUND RADIATION - V. I. Troitsky (Научный вестник МГТУ ГА)
Various informative characteristics of radio thermal fields for generating the standard images in correlation-extremal navigation systems, can be considered as components of a vector field.